2013
DOI: 10.1016/j.molonc.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome instability and carcinogenesis: Insights from murine models of human pancreatic cancer associated with BRCA2 inactivation

Abstract: Chromosomal instability is a hallmark of human cancer cells, but its role in carcinogenesis remains poorly resolved. Insights into this role have emerged from studies on the tumour suppressor BRCA2, whose inactivation in human cancers causes chromosomal instability through the loss of essential functions of the BRCA2 protein in the normal mechanisms responsible for the replication, repair and segregation of DNA during cell division. Humans who carry heterozygous germline mutations in the BRCA2 gene are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…RNA sequencing found that RFXAP and some genes involved in DNA-damage response, such as RAD51, RAD50, BRCA2, RPA2, and POLD3 were upregulated by fisetin. Bioinformatics analysis showed a correlation between RFXAP and DNA repair genes (i.e., RFXAP expression is positively correlated with RAD50, BRCA2, RPA2, and POLD3 expression) [29][30][31][32][33][34][35][36][37][38][39][40][41] . We further explored the role of RFXAP as a transcription factor using ChIP sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA sequencing found that RFXAP and some genes involved in DNA-damage response, such as RAD51, RAD50, BRCA2, RPA2, and POLD3 were upregulated by fisetin. Bioinformatics analysis showed a correlation between RFXAP and DNA repair genes (i.e., RFXAP expression is positively correlated with RAD50, BRCA2, RPA2, and POLD3 expression) [29][30][31][32][33][34][35][36][37][38][39][40][41] . We further explored the role of RFXAP as a transcription factor using ChIP sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…S1D). These genes play important roles in DNA-damage repair, whereas dysregulation of their expression often results in pancreatic cancer gene mutations, chemoradiotherapy resistance, and tumor progression [29][30][31][32][33][34][35][36][37][38][39][40][41] . To further examine the role of RFXAP in PDAC cells with treatment of fisetin, ChIP sequencing was performed in RFXAP-overexpressing PANC-1 (RFXAP-PANC-1) cells to explore the function of RFXAP as a transcription factor.…”
Section: Rfxap Functions In Dna Damage Induced By Fisetinmentioning
confidence: 99%
“…other than aneuploidy. However, appreciation of the role of aneuploidy, or chromosomal instability, as a major driver of carcinogenesis is regaining attention [17][18][19]. Thus, this review is focused on mechanisms related to aneuploidy.…”
mentioning
confidence: 99%
“…Furthermore, Brca2 mutant mice show phenotypic differences in the context of pancreatic cancer GEMMs, dependent on the precise mutation induced and which other genetic events are involved. 25 While it is not fully understood why such large differences in latency and PanIN development have been observed for models involving Brca2 mutation, it is clear that utilizing genetic susceptibility to plan screening regimens needs to take into account many factors.…”
Section: Models Of Inherited Pancreatic Cancer Syndromesmentioning
confidence: 99%